Perkembangan Perencanaan Pembangunan Di Kelurahan Marihat Jaya - Albenopri Simarmata; Romario F D Purba; Dian G Purba; Didi Syahputra; Putri Khairunnisa; Octa P Saragih; Hartati R Sitio; Savirgi B Amri; Brido S Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2024)
Planning is a process for determining appropriate future actions, through a sequence of choices, taking into account available resources. The aim of this study is to identify developments in terms of human resource development, infrastructure development, tourism, health and agricultural development that have been implemented in Marihat Jaya Village. The method used is a descriptive method with the research location in Marihat Jaya Village, Pematangsiantar City. The results of the research findings are limited road infrastructure development in some areas in Marihat Jaya Village, limited health facilities.